2017
DOI: 10.1186/s12879-017-2312-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of selective medium for IMP-type carbapenemase-producing Enterobacteriaceae in stool specimens

Abstract: BackgroundIdentification of carbapenemase-producing Enterobacteriaceae (CPE) in faecal specimens is challenging. This fact is particularly critical because low-level carbapenem-resistant organisms such as IMP-producing CPE are most prevalent in Japan. We developed a modified selective medium more suitable for IMP-type CPE.MethodsFifteen reference CPE strains producing different types of β-lactamases were used to evaluate the commercially available CHROMagar KPC and chromID CARBA as well as the newly prepared M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Enterobacteriaceae strains with minimum inhibitory concentration (MIC) > 2 μg/mL for meropenem were collected and stored at −80°C in phosphate-buffered saline supplemented with 25% glycerol. Isolates were also grown on M-ECC [ 13 ], CHROMagar ECC (CHROMagar Microbiology, Paris, France) supplemented with 0.25 μg/mL meropenem and 70 μg/mL ZnSO 4 , and analyzed using an API 20E system (Sysmex bioMérieux) and an EIKEN dry plate (Eiken Chemical, Tokyo, Japan) to reconfirm species identity and antimicrobial susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…Enterobacteriaceae strains with minimum inhibitory concentration (MIC) > 2 μg/mL for meropenem were collected and stored at −80°C in phosphate-buffered saline supplemented with 25% glycerol. Isolates were also grown on M-ECC [ 13 ], CHROMagar ECC (CHROMagar Microbiology, Paris, France) supplemented with 0.25 μg/mL meropenem and 70 μg/mL ZnSO 4 , and analyzed using an API 20E system (Sysmex bioMérieux) and an EIKEN dry plate (Eiken Chemical, Tokyo, Japan) to reconfirm species identity and antimicrobial susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…But the isolation of CRE from stool specimens is often difficult due to the fact that these strains compose a small proportion of the gut flora and absence of efficient or standardized screening method for their detection makes the process more difficult [32,33]. In addition, it has been shown that surveillance of low level resistance, such as IMP and OXA-48 producers, is difficult and, more often than not, the numbers are underestimated [34,35]. Experience has shown that colonized patients with CRE are often transferred between wards within the same hospital or between different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The drainage canal is not connected directly to the hospital drainage system. Bacteria were collected from water samples (15 ml) by centrifugation at 12,000 ϫ g for 5 min and inoculated onto CHROMagar ECC (CHROMagar, Paris, France) supplemented with 0.25 g/ml of meropenem and 70 g/ml of ZnSO 4 (35), to obtain carbapenem-resistant isolates. All the colonies with different morphologies and colors were stored and subjected to further analysis.…”
Section: Methodsmentioning
confidence: 99%